Analisis Ability To Pay Dan Willing To Pay Upah Tenaga Kerja Berdasarkan Upah Minimum Kabupaten Pada Usaha Mikro Kecil dan Menengah di Kabupaten Mimika - Herlinda, Herlinda; Bakar, Abu (Journal of Economics and Regional Science, 2023)
This study aims to determine the ability to pay and willing to pay labor wages based on district minimum wages for micro, small and medium enterprises in Mimika Regency. The research method used is descriptive research method. In this study the data collection techniques used were questionnaires and documentation. While the analytical instruments used are ATP and WTP. The results of this study indicate that the average ability to pay micro, small and medium enterprises in Mimika Regency is Rp. 2,221,600 while the average willingness to pay micro, small and medium enterprises in Mimika Regency is Rp. 2,753,300